Loan and deposit impact on profitability of islamic and conventional bank in Malaysia / Mohd Shafiq Mohd Asis - Mohd Asis, Mohd Shafiq (2019)
The idea for this study is to examine the Loan and Deposit effect toward the profitability of Islamic and Conventional banks in Malaysia. The relationship between the variable and the bank profitability is examined by employed the ordinary least squares (OLS) regression analysis with a sample of 8 Islamic banks and 8 Conventional banks in Malaysia during the period of 2013-2017. This study reveals that both variables that is net loan and total deposit do not have any significant impact and have a negative relationship with the Islamic bank profitability while for Conventional bank, only total deposit variable that is significant and have a positive relationship with the bank profitability.